Calculation method of dynamic loads spectrum and effects on fatigue damage of a full-scale carbody for high-speed trains. Issue 7 (2nd July 2020) - Lu, Yaohui; Bi, Wei; Zhang, Xing; Zeng, Jing; Chen, Tianli; Wu, Pingbo
Abstract : With the wide application of ballastless track on high-speed railway, the load on the structure of the high-speed train exhibits the characteristics of high frequency and small amplitude. It is the key to analyse the time–frequency characteristics of the track spectrum and to study the efficient and accurate calculation method of the carbody load spectrum. First, the time domain signal estimation of the existing track power spectral density function is carried out, and the influence of the upper and lower limits of different sampling frequencies on the time domain characteristics of the track spectrum is compared and analysed. The frequency response function of vehicle system is calculated by establishing the vehicle vertical system dynamics model. Then it is combined with the track power spectrum density function to calculate the vertical load power spectrum of the carbody, and the carbody load spectrum is obtained through time–frequency domain signal conversion. And the longitudinal load of the carbody is calculated based on the traction braking characteristics of the high-speed train. Finally, the carbody mode is calculated, and then the modal response is used as an excitation to obtain the dynamic stress time history of each node. Combine them with Miner's linear damage accumulation theory to obtain carbody damage. Thereby, the influence of longitudinal load on the fatigue damage of the carbody is compared and analysed.